2014
DOI: 10.1161/jaha.114.001123
|View full text |Cite
|
Sign up to set email alerts
|

Adult Moyamoya Disease in an Urban Center in the United States Is Associated With a High Burden of Watershed Ischemia

Abstract: BackgroundAdult moyamoya disease is rare in the United States, and patients mostly present with cerebral ischemia. However, clinical and neurodiagnostic correlates of ischemia are not well known in this population. We sought to characterize the clinical and radiographic features of moyamoya disease in a large urban center in the United States, with a focus on angiographic and neuroimaging patterns of ischemia.Methods and ResultsWe retrospectively reviewed charts of consecutive adult moyamoya disease patients e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
(36 reference statements)
1
3
1
1
Order By: Relevance
“…Our study supports the findings of Hirano et al in which the authors report that the frequency of stroke risk factors such as HTN, HLD, diabetes, smoking, and alcohol in ischemic, hemorrhagic, and asymptomatic [3,6,9,10].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our study supports the findings of Hirano et al in which the authors report that the frequency of stroke risk factors such as HTN, HLD, diabetes, smoking, and alcohol in ischemic, hemorrhagic, and asymptomatic [3,6,9,10].…”
Section: Discussionsupporting
confidence: 92%
“…Our study supports the findings of Hirano et al in which the authors report that the frequency of stroke risk factors such as HTN, HLD, diabetes, smoking, and alcohol in ischemic, hemorrhagic, and asymptomatic moyamoya groups was not significantly different. Although in our study the stroke risk in asymptomatic moyamoya patients was zero, earlier studies have reported ≥2.4% annual stroke risk in asymptomatic patients [ 3 , 6 , 9 , 10 ].…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Adult patients in Japan with MMS mostly present with hemorrhagic stroke in some old reports [20] in contrast to patients from the United States in whom the ischemic stroke was found to be more common [21]. In a study done on 88 Korean patients, 45% of them had only a single ischemic or hemorrhagic stroke, 55% recurrent attacks mostly ischemic, and 64% of them presented with hemiplegia [22].…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Αποτελέσματα δεν ποικίλει με την ηλικία εμφάνισης. [1039][1040][1041][1042][1043] Η συχνότητα εμφάνισης της εξέλιξης της νόσου σε μία μελέτη ήταν 20% σε ενήλικες ασθενείς με MMD. [1044] Οι γυναίκες ασθενείς είχαν υψηλότερο κίνδυνο εξέλιξης της νόσου από τους άντρες.…”
Section: παθοφυσιολογίαunclassified